Challenges, possibilities, and tensions when investigating child sexual abuse against preschoolers - Magnusson, Mikaela (Justice and recovery for victimised children, 2024)
Investigating and adjudicating sexual abuse against young children is a difficult task for the criminal justice system. The current chapter focuses on challenges, potential possibilities, and tensions at Swedish Barnahus when investigating sexual abuse against preschoolers. By studying legal cases and inquiring Swedish prosecutors and specialist police interviewers, we have identified several challenges that complicate these investigations, such as limited access to corroborative evidence, difficulty conducting child investigative interviews, and challenges in assessing preschoolers’ testimony. Improved interagency collaboration and access to specialised expertise at Barnahus could potentially help alleviate some of these challenges. While the Barnahus model provides promising solutions to help address these challenges when investigating sexual abuse against preschoolers, different tensions currently complicate the realisation of these objectives within the Swedish Barnahus context.